Analysis of the Effect of Word of Mouth on Brand Image and Consumer Purchasing Power of Onitsuka Tiger Shoes - Danil Syahputra; Taufiq Hidayat (International Journal of Economics (IJEC), 2023)
Consumer purchasing power is a decision made by the buyer for the desired goods, especially in terms of brand image or brands that have entered the realm of selection of several alternative choices made by consumers. The image of a brand has a very large role in influencing consumer decisions to buy that product or brand. This study aims to determine the influence of word of mouth as well as brand image and product quality which play a significant role in the decision to buy Onitsuka Tiger shoes at offline official stores. This study uses a quantitative descriptive analysis method with a role to see the role of purchasing decisions from consumers. The results of this study present that these three elements have a very crucial role in the decision to purchase these shoes where a brand image and also product quality provide evidence that this can have a considerable influence on the decision of consumers to buy these products.